Influencing mechanism of strategic flexibility on corporate performance: the mediating role of business model innovation. Issue 3 (27th May 2021) - Xiao, Hongjun; Yang, Zhen; Hu, Yelin
ABSTRACT: This paper explores the internal mechanism of corporate strategic flexibility on corporate performance. Through the empirical test of 197 Chinese enterprises, the empirical test is performed on the statistical hypothesis using the statistical method of SEM and linear regression. We find that the corporate strategic flexibility has a significant positive impact on its financial performance and market performance, and business model innovation has a significant positive impact on corporate financial performance and market performance, and efficiency-centred business model innovation plays a partial mediating role between strategic flexibility (resource flexibility and coordination flexibility) and corporate financial concentration; novelty-centred business model innovation plays a fully mediating role between resource flexibility and corporate market performance, and a partial mediating role between coordination flexibility and corporate market performance.